TELAAH PENGGUNAAN MANHAJ QIRĀ`ĀT AL-MUFASSIRAH TERHADAP PERBEDAAN QIRĀ`ĀT DALAM JUZ ‘AMMA - Siti Nasihatun Ni’mah; Muhammad Najib (STAI AL-ANWAR SARANG, 2023)
This study responds to qirā`āt studies which believe that differences in qirā`āt will give rise to differences in meaning (law). This study is important to carry out in order to prove that differences in qirā`āt do not only give rise to contradictory meanings but these differences in meaning can be synergized. This research is classified as library research, which is a type of qualitative research using descriptive-analytical methods. This research focuses its study on the differences in qirā`āt in Juz 'amma in the farsh ḥurūf aspect which has the potential to give rise to differences in meaning by describing pronunciations that have different qirā`āt based on the agreed boundaries of the seven imams' qirā`āt. Analysis is carried out on pronunciations that have different qirā`āt by analyzing each qirā`ah substance in the nahwu and ṣaraf aspects to clarify its meaning, then combining the meaning of each qirā`ah in a pronunciation into one non-contradiction meaning. The results of this research show that the different meanings of qirā`āt in surah al-Takwīr verse 24 serve to enrich the meaning, the different meanings of qirā`āt in surah al-Fajr verse 18 and surah al-Inshiqāq verse 19 serve to explain the same thing with different editors and the differences in the meaning of qirā`āt in surah al-Nāzi'āt verse 11 and surah al-Balad verses 14 and 15 serve to complement each other.